Haematologic and Urologic Manifestations of Cryptococcus neoformans - Morgan, Jessica; Vardanega, John; Yue, Mimi; Gassiep, Ian (Case Reports in Infectious Diseases, 2024)
Cryptococcus neoformans classically causes pulmonary and central nervous system (CNS) infection in immunocompromised hosts and can lead to disseminated disease. Two cases of atypical cryptococcal infection are presented—an elderly Human Immunodeficiency Virus- (HIV-) negative male with a urinary source of infection and a young HIV-positive male with bone marrow infiltration complicated by haemophagocytic lymphohistiocytosis (HLH). A literature review of systemic cryptococcal infections involving the genitourinary tract and bone marrow was performed. These cases highlight the importance of clinicians considering uncommon manifestations of cryptococcal disease.